Practice dining room. - Unknown:::Creator::::::::::::
Written on verso: "1910-1916; The Practice Dining Room; The Shocks--used after the earthquake 1906 by the Normal School--The new Building furnished in 1910. The new Home Economics department worked into this redwood building and remained until the shocks were burned." The Home Economics building is now the Central Classroom building.